Association between the c.34C > T (rs17602729) polymorphism of the AMPD1 gene and the status of endurance and power athletes: a systematic review and meta-analysis - Kartibou, J.; El Ouali, E. M.; Del Coso, J.; Hackney, A. C.; Rfaki, A.; Saeidi, A.; El Hage, R.; Granacher, U.; Mesfioui, A.; Zouhal, H. (Sports Medicine, 2025)
Background: Previous research has shown that variants in the AMPD1 gene, which encodes the adenosine monophosphate deaminase 1 (AMPD1) protein, may affect energy supply of the muscle and fatigue resistance during high-intensity exercise. A single nucleotide substitution in this gene, specifically a cytosine-to-thymine substitution (c.34C > T; rs17602729), results in a nonsense mutation that causes a deficiency in the AMPD1 protein. Deficiency of the AMPD1 protein due to this polymorphism can influence exercise performance, ultimately affecting the likelihood of reaching the status of elite endurance or power athlete.